2016
DOI: 10.1097/sap.0000000000000619
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction Using the Geometrically Modified Profunda Artery Perforator Flap From the Posteromedial Thigh Region

Abstract: The geometrically modified PAP flap ensures in-the-crease scar positioning and provides sufficient tissue to restore preoperative bra size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 30 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…Studies not relevant (142 articles), cadaver or imaging studies (7 articles), case reports (5 articles), reviews (1 article), and reports in languages other than English (3 articles) were further excluded, resulting in 18 articles for full‐text review. After excluding 10 articles lacking extractable data or with suspected cohort overlap, 8 articles were included in the systematic analysis (Figure 1b) (Allen Jr et al, 2016; Ciudad et al, 2016; Haddock, Gassman, Cho, & Teotia, 2017; Hunsinger et al, 2019; Hunter et al, 2015; Hupkens et al, 2016; Satake et al, 2014; Scaglioni, Chen, Lindenblatt, & Giovanoli, 2017). Individual results of quality assessment items for each studies and the overall appraisals by JBI checklist are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies not relevant (142 articles), cadaver or imaging studies (7 articles), case reports (5 articles), reviews (1 article), and reports in languages other than English (3 articles) were further excluded, resulting in 18 articles for full‐text review. After excluding 10 articles lacking extractable data or with suspected cohort overlap, 8 articles were included in the systematic analysis (Figure 1b) (Allen Jr et al, 2016; Ciudad et al, 2016; Haddock, Gassman, Cho, & Teotia, 2017; Hunsinger et al, 2019; Hunter et al, 2015; Hupkens et al, 2016; Satake et al, 2014; Scaglioni, Chen, Lindenblatt, & Giovanoli, 2017). Individual results of quality assessment items for each studies and the overall appraisals by JBI checklist are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our group previously described the geometrically modified PAP flap with its aim of gaining volume and preventing scar migration. 4 However, especially in patients with a lack of abundance of gluteal tissue, the limiting volume and skin island may be a concern. Moreover, it is preferrable to locate a perforator that is more central in the flap or use the advantages of a mosaic flap: two adjacent flaps with separate pedicles from a single vascular source.…”
Section: Introductionmentioning
confidence: 99%
“…The mean flap weight was 372.4 g in the Hupkens study. 17 Ciudad et al reported the use of a combined TUG and PAP flap to increase the amount of tissue available for medium-to large-sized breast. The mean weight of this composite flap was 466.1 g (range: 390-520 g).…”
Section: Discussionmentioning
confidence: 99%